Impact of digital payments on the economy - Srivastava, Anirudh; Špecián, Petr; Čermáková, Klára; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
Digital payments have peaked the interest of many consumers, businesses and institutions to function as a better payments system in their domestic payments market. Many developing countries in the likes of such as Rwanda, Nigeria, India and Bangladesh, consider digital payments to be beneficial to their countries' economic growth. The aim of this article is to investigate whether digital payments have an impact on the economy of a developed country such as the Czech Republic between 2015 and 2020. Results from the latest available data on digital payments would suggest that there exists an impact but not large enough to change the payment systems used in today's economy. However, the analysis is limited to the latest available data on digital payments from national statistical databases, which are relatively scant and do not take into account all digital payments that would be used in the economy, which motivates further research in this area with more representative data on digital payments used in the economy of the Czech Republic to show the exact impact of these payments system.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses